Investigation of aerodynamic characteristics of a two-bladed sailing wind turbine - Tleubergenova, A. Zh; Tanasheva, N. K.; Shaimerdenova, K. M.; Botpaev, N. K.; Minkov, Leonid L.; Kassiyev, S. B. (Bulletin of the Karaganda university. Physics series)
The article examines a prototype of a wind turbine with two blades. For experimental work, a mock-up of a sailing wind turbine consisting of two blades was developed. The material of the sail blades was selected according to elasticity and lightness, cheapness, roughness of the streamlined surfaces. The study shows the aerodynamic parameters acting on the blade. The air flow velocity varied from 3 to 12 m/s. The dependence of the lifting force and the frontal barrier on the air flow velocity was obtained by turning the blades of the wind turbine so that the angle of attack was α = 00, 150, 300, 450, 600. It is established that when the position of the blade’s changes, the lifting force and the drag force decrease. With an increase in the angle of attack α > 00 leads to a decrease in the midsection of the wind wheel with respect to the air flow. On this basis, there is a decrease in aerodynamic forces. As the speed of the air treacle increases, the speed of rotation of the wind wheel also increases. However, during the experiment it was found that the location of the blades at different angles affects the numerical value of the rotational speed. According to the conducted experiments, several values were obtained. The analysis of the obtained values is carried out. A graph is constructed based on the dependence of the wind wheel rotation frequency on the wind speed with a change in the angle of attack. A wind turbine with blades with a variable angle of attack, which, turning, gradually become more parallel to the direction of the wind. Centrifugal forces regulate the inclination of the blades, and as a result, the speed of rotation of the wind wheel, and keep the wind generator at the nominal speed of rotation.